PENGGUNAAN GAME PEMBELAJARAN BERBASIS WORDWALL UNTUK MENGUKUR KREATIVITAS DAN KONSENTRASI ANAK DI TKQ AL WAHYUHIDAYATULLAH KOTA CILEGON - Khairunnisa, Khairunnisa; benijunedi; Fricticarani, Ade (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2024)
This study aims to determine how to measure children's creativity and concentration using wordwall-based learning games at TKQ Al Wahyu Hidayatullah. This type of research is qualitative research. The population in this study were all class A and B students at TKQ AL Wahyu Hidayatullah, totaling 10 people. The data collection technique in this study was a questionnaire with an interview guide that had 5 questions. The results showed that students were motivated to learn using information technology learning media based on wordwall learning games with results that knew children who began to develop and children who developed as expected. In this study accepted. Based on the results of the research mentioned above, it can be concluded that (1) Wordwall-based learning games can increase the enthusiasm and fun in the classroom of students at TKQ Al Wahyu Hidayatullah and (2) There is an effect of measuring creativity and concentration on children at TKQ Al Wahyu Hidayatullah.